Providing web-based mental health services to at-risk women - Kenny Meghan; Lipman Ellen L; Marziali Elsa (BMC, 2011)
Abstract Background We examined the feasibility of providing web-based mental health services, including synchronous internet video conferencing of an evidence-based support/education group, to at-risk women, specifically poor lone mothers. The objectives of this study were to: (i) adapt a face-to-face support/education group intervention to a web-based format for lone mothers, and (ii) evaluate lone mothers' response to web-based services, including an online video conferencing group intervention program. Methods Participating mothers were recruited through advertisements. To adapt the face-to-face intervention to a web-based format, we evaluated participant motivation through focus group/key informant interviews (n = 7), adapted the intervention training manual for a web-based environment and provided a computer training manual. To evaluate response to web-based services, we provided the intervention to two groups of lone mothers (n = 15). Pre-post quantitative evaluation of mood, self-esteem, social support and parenting was done. Post intervention follow up interviews explored responses to the group and to using technology to access a health service. Participants received $20 per occasion of data collection. Interviews were taped, transcribed and content analysis was used to code and interpret the data. Adherence to the intervention protocol was evaluated. Results Mothers participating in this project experienced multiple difficulties, including financial and mood problems. We adapted the intervention training manual for use in a web-based group environment and ensured adherence to the intervention protocol based on viewing videoconferencing group sessions and discussion with the leaders. Participant responses to the group intervention included decreased isolation, and increased knowledge and confidence in themselves and their parenting; the responses closely matched those of mothers who obtained same service in face-to-face groups. Pre-and post-group quantitative evaluations did not show significant improvements on measures, although the study was not powered to detect these. Conclusions We demonstrated that an evidence-based group intervention program for lone mothers developed and evaluated in face-to-face context transferred well to an online video conferencing format both in terms of group process and outcomes.